The Social Life of Poetry - Green, C. author. aut Link
XV, 279 p.
Keywords: From Jewish publishers to Appalachian poets, Green s cultural study reveals the role of "Mountain Whites" in American racial history. Part One (1880-1935) explores the networks that created American pluralism, revealing Appalachia s essential role in shaping America s understanding of African Americans, Anglos, Jews, Southerners, and Immigrants. Drawing upon archival research and deft close readings of poems, Part Two (1934-1946) delves into the inner-workings of literary history and shows how diverse alliances used four books of poetry about Appalachia to change America s notion of race, region, and pluralism. Green starts with how Jesse Stuart and the Agrarians defended Southern whiteness, follows how James Still appealed to liberals, shows how Muriel Rukeyser put Appalachia at the center of anti-fascism, and ends with how Don West and the Progressives struggled to form interracial labor unions in the South.